Perlindungan Hukum Bagi Pekerja Penyandang Disabilitas - Ulfa Kurnia Sari; Ayesta Intania; Cheeryl Ramadhani Widyanendra Susanto (International Forum of Researchers and Lecturers, 2024)
Getting a job is every person's right to live their life. In terms of getting a job, both normal people and those with disabilities should be able to get the same and decent work without any discrimination. This is in accordance with the body of the 1945 Constitution. This research is related to legal protection for workers with disabilities. The aim of this research is to find out the forms of legal protection for workers with disabilities, as well as to find out the challenges faced in legal protection for workers with disabilities. This research uses a qualitative analysis research method with a literature study approach. The results of this research are regarding legal protection for workers with disabilities regulated in several laws and regulations in Indonesia and international conventions ratified by the Indonesian government. Then the challenges in protecting workers with disabilities include stigma and discrimination, lack of public awareness, lack of access to infrastructure for people with disabilities, lack of regulations and limited types of work. This is a challenge in providing protection to workers with disabilities.